Does Patient Sex Influence Cartilage Surgery Outcome?: Analysis of Results at 5-Year Follow-up in a Large Cohort of Patients Treated With Matrix-Assisted Autologous Chondrocyte Transplantation. (August 2013) - Filardo, Giuseppe; Kon, Elizaveta; Andriolo, Luca; Vannini, Francesca; Buda, Roberto; Ferruzzi, Alberto; Giannini, Sandro; Marcacci, Maurilio
Background: Sexual dimorphism in humans has already been documented at different levels, and preliminary findings also suggest the importance of patient sex on clinical outcome in the treatment of cartilage lesions. Purpose: To document and analyze the influence of sex on clinical outcome in a large cohort of patients treated with a cartilage regenerative procedure for knee chondral lesions and prospectively followed at midterm follow-up. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 250 knees were treated with matrix-assisted autologous chondrocyte transplantation (MACT) and prospectively evaluated with International Knee Documentation Committee (IKDC), EuroQol visual analog scale (EQ-VAS), and Tegner scores at 1-, 2-, and minimum 5-year follow-ups to compare results obtained in men and women. The lesions were focal International Cartilage Repair Society grade III-IV chondral knee defects involving femoral condyles, trochleae, and patellae. Two homogeneous groups of 56 male patients and 56 female patients were then selected by a blinded statistician for a matched-pair analysis. Results: A statistically significant improvement in all the scores in both men and women was observed in the general population. The IKDC subjective score showed better results for men at all follow-up times: at 5 years, the mean IKDC subjective score was 79.5 ± 18.6 versus 64.3 ± 20.2 for men and women, respectively ( P < .0005), and the same trend was confirmed with the EQ-VAS and Tegner scores. The matched-pair analysis confirmed the difference of final results achieved (74.1 ± 19.8 vs 63.7 ± 20.2, respectively; P = .006). However, men and women started with different preoperative levels, and the analysis of the improvement obtained was not significantly different. Finally, when scores were standardized for each patient, according to the mean score typical for the corresponding age and sex category in a healthy population, a sex-related difference was not confirmed at any of the follow-ups. Etiological factors, lesion site, and preinjury activity level differed in women and men of the general population and were the confounding factors responsible for the different outcome not confirmed by the analysis of homogeneous cohorts of patients. Conclusion: Women have a different knee chondral lesion pattern and more often have unfavorable conditions related to the cause of injury, site, and activity level, and they also have lower raw, not standardized, scores. However, a matched-pair analysis with data standardized for the specific patient categories showed that, on equal terms, women have the same possibilities for successful outcome as men after surgical treatment for knee cartilage regeneration.